Analysis of Waste Processing Reduce Reuse and Recycle to Reduce the Burden of Waste Accumulation in Bekasi City - Saleh, Abdul; Purwanto, Moh Yanuar Jarwadi; Pravitasari, Andrea Emma (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2025)
Waste management in large cities like Bekasi is a major challenge in achieving sustainable development. The implementation of the 3R concept (Reduce, Reuse, Recycle) through 3R-Based Waste Processing Sites (TPS3R) has become a key solution. This study analyzes five TPS3Rs in Bekasi City: Bina Lindung, Prima Harapan, Sakura Regency, Mustika Sari, and Ciketing Udik. The objective is to assess the amount of waste, observe the processing methods, and formulate waste management strategies using both quantitative and qualitative methods. Samples were collected from varying numbers of households. TPS3R Bina Lindung and Sakura Regency each sampled 80 households, including a mix of permanent, semi-permanent, and non-permanent homes. TPS3R Prima Harapan sampled 28 households, Mustika Sari 160 households, and Ciketing Udik 49 households. The results show varying levels of waste management effectiveness. Mustika Sari achieved the highest effectiveness at 97.58%, followed by Sakura Regency at 92.39%, Prima Harapan at 50%, Ciketing Udik at 5.71%, and Bina Lindung at 2.67%. SWOT analysis reveals that the success of waste management is highly influenced by the reuse of recyclable materials. However, weaknesses include a lack of public awareness and low community participation in environmental initiatives. There is significant potential in community support, particularly in reducing paper, plastic, and bottle waste. On the other hand, challenges include limited training for TPS3R operators and the infrequent processing of organic waste by residents.